2005
DOI: 10.4049/jimmunol.175.3.1686
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Effector CD8+ T Cell Generation with Enhanced Granzyme B Expression by IL-27

Abstract: IL-27 is a novel IL-12 family member that plays a role in the early regulation of Th1 initiation. We have recently demonstrated that IL-27 has a potent antitumor activity, which is mainly mediated through CD8+ T cells, and also has an adjuvant activity to induce epitope-specific CTL in vivo. In this study, we further investigated the in vitro effect of IL-27 on CD8+ T cells of mouse spleen cells. In a manner similar to CD4+ T cells, IL-27 activated STAT1, -2, -3, -4, and -5, and augmented the expression of T-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 29 publications
10
135
1
Order By: Relevance
“…It has been shown that IL-27 not only augments the expression of Th1-specific factors (T-bet and IL-12R␤2) and activities of CTLs, but also down-regulates expression of the Th2-specific factor GATA-3 in vitro and in vivo (4). Studies show that the antitumor effects by IL-27 are not dependent on IL-12-mediated signaling (43). IL-12 can cause severe cytotoxicity in vivo such as splenomegaly and liver injury due to the prolonged induction and maintenance phases of Th1 effectors (42,44).…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that IL-27 not only augments the expression of Th1-specific factors (T-bet and IL-12R␤2) and activities of CTLs, but also down-regulates expression of the Th2-specific factor GATA-3 in vitro and in vivo (4). Studies show that the antitumor effects by IL-27 are not dependent on IL-12-mediated signaling (43). IL-12 can cause severe cytotoxicity in vivo such as splenomegaly and liver injury due to the prolonged induction and maintenance phases of Th1 effectors (42,44).…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with a recently published report by Tanabe et al (33) demonstrating a strong mitogenic effect of INF-␣␤ on STAT1-deficient but not wild-type T cells. However, Liang et al (42) have shown that STAT1 is required for IFN-␣-mediated NK cell cytotoxicity, and Morishima et al (43) have shown that IL-27-mediated CD8 T cell up-regulation of granzyme B and perforin is also dependent on STAT1. Thus, STAT1 appears to play a complex role in the regulation of cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor, Stat1 plays an important role in antiviral responses by inducing expression of antiviral IFN-stimulated genes and epitope-specific CTLs, and Stat1-null mice exhibit enhanced susceptibility to bacterial and viral infections (32)(33)(34). Based on these studies, together with a recent study showing that miR-146a impairs both AP-1 activity and IL-2 expression induced by TCR engagement (13), our current work suggests that upregulation of miR-146a in CHB may lead to decreased expression of antiviral cytokines, antiviral IFN-stimulated genes, and the lytic function of T cells by targeting Stat1, thus promoting T cell functional deficiency and immune tolerance to HBV infection.…”
Section: Discussionmentioning
confidence: 99%